ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI IMPOR MINYAK BUMI MENTAH INDONESIA - Putri, Ega Gusdwi; Kartika, Endra (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 10 (2022): vol.11.10. OKTOBER 2022 [3701 - 4009], 2022)
Crude oil is an important source of energy in every country, especially in industrialists. This energy can drive the manufacturing sector of a country to get the desired output. It can be seen that this crude oil is one of the main commodities imported by Indonesia from year to year and imports of petroleum are relatively high. This study aims to analyze the factors affecting imports of crude oil in Indonesia in 2001-2020 using gravity with the variables Price, Exchange Rate, Production and Foreign Exchange Reserves. The research location was conducted in Indonesia because this research discussed the determinants of Indonesian crude oil imports. The type of data used in this research is secondary data. The analytical method in this study is the Error Correction Model used to overcome the problem of non-stationary data. The results of this study The price of crude oil, exchange rates, production, and foreign exchange simultaneously affect imports of crude oil in Indonesia. Crude oil prices, production, and foreign exchange reserves partially have a positive and significant effect both in the long and short term on the import of crude oil in Indonesia. While the exchange rate has no effect in the long term, it has a positive and significant effect in the short term on imports of crude oil in Indonesia.